Non‐vitamin K antagonist oral anticoagulants versus warfarin for cardioversion of atrial fibrillation in clinical practice: A single‐center experience. Issue 1 (1st June 2016) - Shibata, Naoki; Morishima, Itsuro; Okumura, Kenji; Morita, Yasuhiro; Takagi, Kensuke; Yoshida, Ruka; Nagai, Hiroaki; Tomomatsu, Toshiro; Ikai, Yoshihiro; Terada, Kazushi; Tsuzuki, Kazuhito; Tsuboi, Hideyuki; et al.
Abstract: Background: Anticoagulation therapy with the vitamin K antagonist (VKA) warfarin has been demonstrated to reduce thromboembolic risk after electrical cardioversion (ECV). However, data concerning ECV with non‐VKA oral anticoagulants (NOACs) is limited. The objective of this study was to determine the efficacy and safety of NOACs in patients undergoing ECV in a real‐world clinical practice at a single center in Japan. Methods: We retrospectively analyzed the data of 406 consecutive patients who underwent ECV for atrial fibrillation (AF) or flutter under anticoagulation with one of the three NOACs ( n =149) or with a VKA ( n =257). Results: The CHADS2 and HAS‐BLED scores were significantly higher in the VKA group, whereas the NOACs group had a tendency toward greater spontaneous echo contrast grades. After ECV, ischemic stroke occurred in three patients of the VKA group and one patient in the NOAC group, all of whom had persistent AF, indicating no significant difference in the thromboembolic event rate within 30 days following ECV. No other thromboembolic events, major bleeding, or death occurred in either group. Among the NOAC and VKA patients in whom we newly introduced an oral anticoagulant to perform ECV, the number of days leading to ECV was significantly lesser for the NOAC patients. Conclusion: NOACs may be used as an alternative to VKAs for ECV and may allow prompt ECV in clinical practices.